A Peculiar Peritoneum: A Case of Tuberculosis in a Male Without Known Risk Factors. (December 2022) - Wynne, Joshua; Chew, Kimberline; Kothari, Pooja; Bressman, Maxwell; Tow, Clara
Peritoneal tuberculosis is an uncommon diagnosis in developed countries and most commonly presents in patients with known risk factors for tuberculosis. We report a case of a patient without tuberculosis risk factors who presented with 4 years of intermittent fevers, several weeks of increasing abdominal distention, and newly discovered elevated liver tests. The diagnosis of peritoneal tuberculosis was confirmed following an extensive workup with a positive ascitic fluid culture for Mycobacterium tuberculosis . The patient's fevers resolved with antibiotic therapy, and antibiotic therapy was subsequently de-escalated based on the susceptibility profile.